(untitled) (Educational Dimension, 2024)
Developing a competent personality involves conceptualising the content of language education. In implementing the New Ukrainian School reform, many problematic issues arise regarding the practical reorientation to new standards. Special attention needs to be paid to the organisation of the educational activities of male and female students, in which their integrated ability to apply acquired knowledge in life situations is formed. The research of linguists is focused on developing interconnected ways of combining the subject and key competencies of learners, which contribute to their successful socialisation in society. Considering educational requirements makes it necessary to highlight the methodological potential of forming mathematical competence as a component of linguistic personality. The following methods were used to solve the outlined tasks: analysis and synthesis of scientific research, induction and deduction to determine the categorical concept and substantiation of the theoretical and methodological foundations of the problem. The article analyses modern approaches and principles of language learning, particularly Ukrainian syntax. The concept of "mathematical competence of secondary school students in learning the syntax of the Ukrainian language" has been interpreted. The system of didactic tools for forming students’ mathematical competence has been organised. The results of the conducted research are the basis of the professional activities of the lexicographer in the lessons in the preparation of harmoniously developed students of general secondary education institutions.